2005
DOI: 10.1038/sj.leu.2404032
|View full text |Cite
|
Sign up to set email alerts
|

Absolute lymphocyte count recovery after induction chemotherapy predicts superior survival in acute myelogenous leukemia

Abstract: Absolute lymphocyte count (ALC) recovery postautologous stem cell transplantation is an independent predictor for survival in acute myelogenous leukemia (AML). The role of ALC recovery after induction chemotherapy (IC) in AML is unknown. We hypothesize that ALC recovery after IC has a direct impact on survival. We have now evaluated the impact of ALC recovery after IC on overall survival (OS) and leukemia-free survival (LFS) in 103 consecutive, newly diagnosed AML patients treated with standard IC and consolid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
74
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(80 citation statements)
references
References 13 publications
6
74
0
Order By: Relevance
“…Behl et al 15 demonstrated that ALC is predictive of outcome in older adults with AML (median age 59 years). Through comparison with our dataset, we observe that in our younger population (median age 18 years) ALC has a more dramatic predictive ability (HR 4.9 vs 2.1) and a lower ALC cutoff (350 vs 500 cells/lL).…”
Section: Discussion Alc Is An Independent Prognostic Indicator In Acumentioning
confidence: 99%
See 1 more Smart Citation
“…Behl et al 15 demonstrated that ALC is predictive of outcome in older adults with AML (median age 59 years). Through comparison with our dataset, we observe that in our younger population (median age 18 years) ALC has a more dramatic predictive ability (HR 4.9 vs 2.1) and a lower ALC cutoff (350 vs 500 cells/lL).…”
Section: Discussion Alc Is An Independent Prognostic Indicator In Acumentioning
confidence: 99%
“…[11][12][13][14] These results suggest that rapid lymphocyte engraftment in these patients could increase a graft-versus-cancer effect and/or decrease morbidity related to poor engraftment. Interestingly, Behl et al 15 found that absolute lymphocyte counts (ALC) after induction chemotherapy predicts improved survival in adult patients with AML, suggesting that lymphocyte levels are critical in the nontransplant setting also. Two meeting abstracts suggested that lymphocyte counts after chemotherapy may also be predictive of survival in the pediatric age group.…”
Section: Lymphocytes In Cancermentioning
confidence: 99%
“…For example, shift reconstitution of the immune system after induction regimens correlates with improved survival, and absolute leukocyte count is an independent prognostic factor for survival in patients with acute leukemia [14]. What is more, it is proven that malignant cells use multiple pathways to interfere the host immune system promoting the number and function of regulatory T cells (T regs) and subsequently reducing the ability of cytotoxic T cells to target leukemia [17].…”
Section: Rationale For Immunotherapy In Acute Leukemiamentioning
confidence: 99%
“…Similar expansions of immune cells have been observed in other hematological malignancies and this increase of immune cells has been associated with a better prognosis of patients. Thus, higher absolute lymphocyte count predicts higher survival in lymphoma, acute myeloblastic leukemia and myeloma (Cox et al, 2008;Siddiqui et al, 2006;Porrata et al, 2007Porrata et al, , 2009RayCoquard et al, 2009;De Angulo et al, 2008;Behl et al 2006Behl et al , 2007Ege et al, 2008). NK cell count has also been associated with clinical outcome in patients with diffuse large B-cell lymphoma (Plonquet et al, 2007).…”
Section: Immune Surveillance Of Chronic Lymphocytic Leukemiamentioning
confidence: 99%